2015
DOI: 10.1139/cjm-2015-0129
|View full text |Cite
|
Sign up to set email alerts
|

Vertical distribution of Fe and Fe(III)-reducing bacteria in the sediments of Lake Donghu, China

Abstract: Abstract:In lake sediments, iron (Fe) is the most versatile element, and the redox cycling of Fe has a wide influence on the biogeochemical cycling of organic and inorganic substances. The aim of the present study was to analyze the vertical distribution of Fe and Fe(III)-reducing bacteria (FeRB) in the surface sediment (30 cm) of Lake Donghu, China. At the 3 sites we surveyed, FeRB and Fe(II)-oxidizing bacteria (FeOB) coexisted in anoxic sediments. Geobacter-related FeRB accounted for 5%-31% of the total Bact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 59 publications
(77 reference statements)
0
4
2
Order By: Relevance
“…6 However, so far, information about their roles in fresh lake sediments has been very limited. 25 A recent work revealed that EEB were largely involved in the biogeochemical Fe cycling in hypersaline sediments of a salt lake, 12 but their abundance in hypersaline sediments was much lower than that in fresh lake sediments obtained in this study. Such a difference implies that EEB might be involved in the degradation of organic matter and possibly biogeochemical cycling of other elements in fresh environments.…”
Section: Environmental Science and Technology Letterscontrasting
confidence: 58%
See 1 more Smart Citation
“…6 However, so far, information about their roles in fresh lake sediments has been very limited. 25 A recent work revealed that EEB were largely involved in the biogeochemical Fe cycling in hypersaline sediments of a salt lake, 12 but their abundance in hypersaline sediments was much lower than that in fresh lake sediments obtained in this study. Such a difference implies that EEB might be involved in the degradation of organic matter and possibly biogeochemical cycling of other elements in fresh environments.…”
Section: Environmental Science and Technology Letterscontrasting
confidence: 58%
“…was also strongly affected by the phosphorus level. 25 This result implies that abundant EEB might inhabit in eutrophic freshwater lakes.…”
Section: ■ Results and Discussionmentioning
confidence: 93%
“…Surface sediments were collected in October 2018 from Lake Dianchi, a eutrophic lake located in Kunming, P. R. China (24°40′–25°02′N, 102°36′–103°40′E), using the method described by Tian et al (2015). Surface sediments were sealed in sterile plastic bags, transported to the laboratory, homogenized and then used for experiments.…”
Section: Methodsmentioning
confidence: 99%
“…Surface sediment was collected in May 2018 from Dianchi Lake, located in Kunming, China (102°38ʹ0.84ʹʹE, 24°58ʹ41.61ʹʹN) using specifi c sampling methods described previously by Tian et al (2015). Surface sediment cores were sampled to a depth of 20 mm and carefully transferred to PVC cylinders in situ (30 mm diameter × 110 mm high) before being subject to laboratory microcosm incubations.…”
Section: Experimental Designmentioning
confidence: 99%